Collective Optimism and Selection Against Male Twins in Utero. (27th February 2020) - Catalano, Ralph A.; Goldman-Mellor, Sidra; Karasek, Deborah A.; Gemmill, Alison; Casey, Joan A.; Elser, Holly; Bruckner, Tim A.; Hartig, Terry
Abstract: Scholarly literature claims that health declines in populations when optimism about investing in the future wanes. This claim leads us to describe collective optimism as a predictor of selection in utero. Based on the literature, we argue that the incidence of suicide gauges collective optimism in a population and therefore willingness to invest in the future. Using monthly data from Sweden for the years 1973–2016, we test the hypothesis that the incidence of suicide among women of child-bearing age correlates inversely with male twin births, an indicator of biological investment in high-risk gestations. We find that, as predicted by our theory, the incidence of suicide at month t varies inversely with the ratio of twin to singleton male births at month t + 3. Our results illustrate the likely sensitivity of selection in utero to change in the social environment and so the potential for viewing collective optimism as a component of public health infrastructure.